The bad idea and other stories [book with audioplayer] - Pizzoli, Greg (Pizzoli, Greg. Earl & Worm., 2025)
Earl, a cheerful bird who loves playing saxophone, and Worm, a quiet bookworm, overcome their differences with lemonade, creativity, and sharing their stories, becoming the best of friends.